Mental health disorders and utilization of mental healthcare services in United Nations personnel. (2020) - Brown, Adam D.; Schultebraucks, Katharina; Qian, Meng; Li, Meng; Horesh, Danny; Siegel, Carol; Brody, Yosef; Amer, Abdalla Mansour; Lev-Ari, Rony Kapel; Mas, Francis; Marmar, Charles R.; Farmer, Jillann
Abstract: Background: United Nations (UN) personnel address a diverse range of political, social, and cultural crises throughout the world. Compared with other occupations routinely exposed to traumatic stress, there remains a paucity of research on mental health disorders and access to mental healthcare in this population. To fill this gap, personnel from UN agencies were surveyed for mental health disorders and mental healthcare utilization. Methods: UN personnel ( N = 17 363) from 11 UN entities completed online measures of generalized anxiety disorder (GAD), major depressive disorder (MDD), posttraumatic stress disorder (PTSD), trauma exposure, mental healthcare usage, and socio-demographic information. Results: Exposure to one or more traumatic events was reported by 36.2% of survey responders. Additionally, 17.9% screened positive for GAD, 22.8% for MDD, and 19.9% for PTSD. Employing multivariable logistic regressions, low job satisfaction, younger age (<35 years of age), greater length of employment, and trauma exposure on or off-duty was significantly associated with all the three disorders. Among individuals screening positive for a mental health disorder, 2.05% sought mental health treatment within and 10.01% outside the UN in the past year. Conclusions: UN personnel appear to be at high risk for trauma exposure and screening positive for a mental health disorder, yet a small percentage screening positive for mental health disorders sought treatment. Despite the mental health gaps observed in this study, additional research is needed, as these data reflect a large sample of convenience and it cannot be determined if the findings are representative of the UN.